A review of Integrated Area Development (IAD) projects - Cariño, Benjamin V. (The Philippine Review of Business and Economics, 1997)
This paper examines the Integrated Area Development Approach (IAD) and its potential as a mechanism for influencing Local Government Units (LGUs) to address national concerns at local levels, and as a tool for reducing sub-national disparities in welfare through intergovernmental transfers of financial resources. A major finding of this study is that IAD strategy continues to be a valid approach for achieving the redistribution and equity objectives of the national government. However, institutional capacity-building efforts must be exerted, and more efficient intergovernmental resource transfer mechanisms must be put in place if LGUs have to assume the planning and implementation of IAD projects.